سورہ بقرہ میں عبادات سے متعلق فقہی مباحث: عربی تفاسیرکا تجزیاتی مطالعہ: Jurisprudential Debates on Worship in Surah Baqarah: An Analytical Study of Arabic Tafāsīr - Tasleem, Muhammad; Ali, Dr. Asjad; Aleem, Dr. Abdul (Al-Amīr Research Journal for Islamic Studies, 2024)
Allah Almighty has created this universe and all the creatures that live in it for a purpose, one of those creations is humans and jinn and Allah Almighty has also created them for a specific purpose and that purpose. Worshiping Allah Almighty is the duty of man to whom Allah Almighty sent the Prophets and Messengers to invite them and then sent down books and scriptures from the sky to them so that they would continue to draw attention to the worship of God and remind them of it. Stay. Last of all, Hazrat Muhammad ﷺ came to whom Allah revealed his last book, the Holy Qur’an, whose teachings are for all mankind until the Day of Judgment. The first and greatest Surah of the Holy Quran is Surah Al-Baqarah, in which worship has been mentioned in detail. Among these prayers, fasting, zakat and Hajj, which will be mentioned in detail in this article. And along with the Arabic commentators. Keeping in view the opinions, the truth of all the problems related to worship will be revealed. Keywords: Surah Al-Baqarah, Qur’an, Jurisprudential, Worshiping, Mufassirin.